Rescuing Local Wisdom in an Era of Anthropogenic Climate Change: A Quest for Ultimate Reality - Hani Hasanah; Teuku Fajar Shadiq (Green Publisher Indonesia, 2025)
This research aims to explore the role and relevance of local wisdom in facing the impacts of human-induced (anthropogenic) climate change. The main focus of this research is to identify how knowledge and practice of The local community can assist the community in adapting to the increasing environmental challenges. This research method uses a descriptive qualitative approach. Agriculture in Jayapura Regency is generally a plantation. Central Maluku is a plantation area which is generally a smallholder plantation. While in Manggarai Regency, dry land agriculture is common. Climate change projections in Jayapura Regency show a tendency to shift. While in Yapen Regency, Kaimana Regency, Maluku Regency, Maybrat Regency, West Halmahera Regency and Central Maluku Regency do not show any significant changes compared to baseline conditions. And in Kabupaten Manggarai there is the potential for climate change. Regional vulnerability was conducted at TEKAD target locations. In general, the level of village vulnerability is quite varied from non-vulnerable villages to vulnerable villages. Adaptation options in general that can be done include controlling drought, floods, landslides, improving farming and increasing food security, building and managing food granaries, strengthening community capacity, handling sea level rise, sea water abrasion and high waves.